2022
DOI: 10.1111/dom.14633
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a 6‐month, low‐carbohydrate diet on glycaemic control, body composition, and cardiovascular risk factors in patients with type 2 diabetes: An open‐label randomized controlled trial

Abstract: Aim: To investigate the efficacy and safety of a non-calorie-restricted lowcarbohydrate diet (LCD) on glycaemic control, body composition, and cardiovascular risk factors in patients with type 2 diabetes (T2D) instructed to maintain their noninsulin antidiabetic medication and physical activity. Materials and Methods:In an open-label randomized controlled trial, patients with T2D were randomized 2:1 to either a LCD with a maximum of 20 E% (percentage of total energy intake) from carbohydrates (n = 49) or a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 40 publications
(144 reference statements)
2
28
0
1
Order By: Relevance
“…Episodic future thinking during delay discounting tasks reduces the rate of discounting (i.e., reduction of impulsive choices) and increases the functional coupling of the ACC-hippocampus/amygdala ( 63 ). This finding is also in agreement with others showing the role of the parahippocampal gyrus in procrastination ( 71 ). Coupling between the PFC, including the ACC and hippocampal regions, is also engaged during mental simulations involving future scenarios.…”
Section: Introductionsupporting
confidence: 94%
See 2 more Smart Citations
“…Episodic future thinking during delay discounting tasks reduces the rate of discounting (i.e., reduction of impulsive choices) and increases the functional coupling of the ACC-hippocampus/amygdala ( 63 ). This finding is also in agreement with others showing the role of the parahippocampal gyrus in procrastination ( 71 ). Coupling between the PFC, including the ACC and hippocampal regions, is also engaged during mental simulations involving future scenarios.…”
Section: Introductionsupporting
confidence: 94%
“…For example, the consumption of different macronutrients such as carbohydrates and fats triggers the different hormonal response ( 70 ). In fact, low-carbohydrate diet have a great impact on weight loss and weight control ( 71 , 73 ). Research addressing active and passive risk taking should benefit from examining the impact initiatory behaviors regarding dietary choices and also physical activity and their associated hormonal response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 A high-protein diet can reduce HbA1c levels in T2DM patients but increase the frequency of gastrointestinal symptoms such as diarrhea and constipation with abnormal stool consistency. 34 According to our study, abnormal stool consistency can increase ImP, which explains why ImP is positively correlated with the intake of cheese, milk and eggs.…”
Section: Discussionmentioning
confidence: 58%
“…In addition to glycemic control, since insulin resistance in patients with T2DM increases the eagerness for carbohydrate intake, dietary interventions that reduce dietary carbohydrate intake are thought to improve glycemic control and T2DM outcomes (Gram-Kampmann et al, 2022). Interventional studies have shown that low-carbohydrate diet improves glycemic control and leads to reductions in cardiovascular disease risk in people with T2DM (Han et al, 2021).…”
Section: Introductionmentioning
confidence: 99%